Cost-effectiveness analysis of trifluridine/tipiracil combined with bevacizumab vs. monotherapy for third-line treatment of colorectal cancer - Huang, Long-Zhuan; Chen, Ya-Qing; Gu, Hang-Ye; Chen, Yong (Frontiers in Public Health, 2024)
BackgroundThe combination of trifluridine/tipiracil (FTD/TPI) and bevacizumab has demonstrated promising efficacy and safety in the treatment of colorectal cancer (CRC). This study aims to evaluate the cost-effectiveness of trifluridine/tipiracil combined with bevacizumab vs. trifluridine/tipiracil monotherapy as a third-line treatment regimen for colorectal cancer within the Chinese healthcare system, providing an economic basis for clinical application.MethodsBased on data from the SUNLIGHT Phase III clinical trial, a dynamic Markov model was constructed with a cycle length of 4 weeks and a simulation duration of 10 years. Direct medical costs and quality-adjusted life years (QALYs) were calculated. The incremental cost-effectiveness ratio (ICER) was compared with the willingness-to-pay threshold (WTP = ¥268,200.00/QALY) to assess the economic viability of the treatment regimen. One-way sensitivity analysis and probabilistic sensitivity analysis were conducted to verify the robustness of the model results.ResultsThe cost of trifluridine/tipiracil combined with bevacizumab treatment (¥838,492.74) was higher than that of trifluridine/tipiracil monotherapy (¥357,396.97), with greater health benefits (2.45 QALYs vs. 1.54 QALYs). The ICER was ¥527,577.36/QALY, exceeding the willingness-to-pay threshold. One-way sensitivity analysis indicated that drug costs and utility values during the progression-free period significantly impacted model outputs. Probabilistic sensitivity analysis further confirmed the robustness of the results, showing that at a willingness-to-pay threshold of ¥494,000.00, the probability of the combined treatment being cost-effective was 50%.ConclusionTrifluridine/tipiracil combined with bevacizumab, as a third-line treatment for colorectal cancer, does not have a cost-effectiveness advantage compared to trifluridine/tipiracil monotherapy in economic evaluations.